Penerapan Narasi Ekspositoris dalam Penulisan Naskah Video Dokumenter “Jejak yang Tersulam di Balik Motif Batik Rumah Gajah Mungkur” - Windy Nur Octaliya; Priyo Subekti; Gumgum Gumilar (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
Batik is an Indonesian cultural heritage recognized by UNESCO as an Intangible Cultural Heritage of Humanity on 2 October 2009. One local batik rich in historical and philosophical value yet lacking audio-visual documentation is Batik Gajah Mungkur from Gresik, East Java, particularly the Rumah Gajah Mungkur motif, an exclusive design not owned by any other batik producer in Gresik. This final project aims to analyze the creative process of the documentary video